Mental Health Consequences for Healthcare Workers During the COVID-19 Pandemic: A Scoping Review to Draw Lessons for LMICs - Moitra, Modhurima; Rahman, Muhammad; Collins, Pamela Y.; Gohar, Fatima; Weaver, Marcia; Kinuthia, John; Rössler, Wulf; Petersen, Stefan; Unutzer, Jurgen; Saxena, Shekhar; Huang, Keng Yen; Lai, Joanna; et al. (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has had a significant impact on the mental health of healthcare workers (HCWs) particularly in low-resourced settings. This scoping review provides a summary of current evidence on the mental health impacts of COVID on HCWs. Methods: A scoping review was conducted searching PubMed and Embase for articles relevant to mental health conditions among HCWs during COVID-19. Relevant articles were screened and extracted to summarize key outcomes and findings. Results: A total of fifty-one studies were included in this review. Depressive symptoms, anxiety symptoms, trauma, insomnia and sleep quality, workplace burnout and fatigue, and distress were the main outcomes reviewed. Most studies found a high number of symptoms endorsed for depression, anxiety, and other conditions. We found differences in symptoms by sex, age, and HCW role, with female, younger-aged, frontline workers, and non-physician workers being affected more than other subgroups. Conclusion: This review highlights the existing burden of mental health conditions reported by HCWs during COVID-19. It also demonstrates emerging disparities among affected HCW subgroups. This scoping review emphasizes the importance of generating high quality evidence and developing informed interventions for HCW mental health with a focus on LMIC settings.